Efficient and Fully Scalable Encryption for MPEG-4 FGS - Yuan, Chun; Zhu, Bin Benjamin; Wang, Yidong; Li, Shipeng; Zhong, Yuzhuo (IEEE Int. Symp. Circuits and Systems, 2003)
The newly adopted MPEG-4 Fine Granularity Scalability (FGS) video coding standard offers full scalability to enable easy and flexible adaptation to changing constraints and different requirements. Encryption of an FGS stream should preserve the full scalability. In this paper, we propose a novel and low complexity scheme to encrypt MPEG-4 FGS streams which enables full FGS functionalities. The encrypted FGS stream can be processed by middle stages directly on the ciphertext without decryption. In addition, the proposed scheme has no degradation on either FGS compression efficiency or error resilient performance, and allows random access. Experimental results as well as a preliminary security analysis of the proposed scheme are also included in this paper.